Practice theory in practice: critical anthropology in Galicia and Portugal in the 1970s - O'neill, B. J. (2017)
What links are there between feldwork sites and the specifc authors, texts, and theories which inspired the ethnographer before and after the stint? Here are some retrospective meanderings on two terrains studied in the 1970s – the Caurel mountains in eastern Galicia and north-eastern Trás-os-Montes in Portugal. Neither of these places seemed to ft anywhere within the expansive British anthropology of the Mediterranean dominant throughout that decade. These hamlets certainly looked nothing like minuscule, egalitarian rural paradises. Dual family structures, complex household dynamics, asymmetrical labour exchanges, alternative marriages, and rampant bastardy required a radically different analysis. Inspiration came from Goody’s comparative sociology of Eurasian inheritance strategies and Bourdieu’s practice theory. My earlier undergraduate work on realist literature and descriptive dissection now heard – following the feldwork itself – a loud echo. Both Goody’s and Bourdieu’s rebel and pervasive hyper-critical spirits provided the spark.